Clarifying the association between Parkinson’s disease and vitiligo: a population-based large-scale study - Kridin, Khalaf; Ofir, Lior; Weinstein, Orly; Badarny, Samih (Frontiers in Neurology, 2024)
Objective Our knowledge about the association between vitiligo and Parkinson’s disease (PD) is sparse. We sought to investigate the bidirectional epidemiological association between vitiligo and PD. Methods A population-based study was conducted using Clalit Health Services (CHS) database (2002–2019) using both a cohort study and a case–control study design. Adjusted hazard ratio (HR) and odds ratio (OR) were calculated by multivariate Cox and logistic regressions, respectively. Results Overall, 20,851 vitiligo patients and 102,475 controls were included. The incidence of new-onset PD was 2.9 (95% CI, 2.1–4.1) and 4.3 (95% CI, 3.8–4.9) cases per 10,000 person-years among patients with vitiligo and controls, respectively. Patients with vitiligo had a significantly decreased risk of developing new-onset PD [adjusted HR, 0.62; 95% confidence interval (CI), 0.43–0.89, p = 0.009]. On the other hand, the likelihood of having vitiligo after a preexisting diagnosis of PD was not statistically different (adjusted OR, 0.80; 95% CI, 0.61–1.06; p = 0.117). Relative to the remaining patients with vitiligo, those with vitiligo and comorbid PD experienced an elevated risk of all-cause mortality (adjusted HR, 2.63; 95% CI, 1.82–3.80; p < 0.001) and higher prevalence of cardiometabolic comorbidities. Conclusion Vitiligo is associated with a lower risk of developing PD. The presence of comorbid PD predisposes patients with vitiligo to elevated mortality and cardiometabolic outcomes.